(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to highlight the income tax by direct deduction in Iraq and the most important problems and obstacles faced by this type of taxes and identify the reasons for the clear and striking differences in the deduction between those charged with the state departments to reach the exact calculation in accordance with the laws and instructions and the unification of tax deductions for similar cases and clarify Cases of confusion and ambiguity, and achieving justice by deduction, whether in favor of the taxpayer or financial authority. Under the laws and regulations in force. The study was conducted on a sample of the salaries of the employees of the University of Basra, and interviews with account managers and audit managers. Where the most important factors leading to this difference and difference were reached, which is considered one of the most important reasons is the low professional efficiency of accountants who are underwriting and the scrutiny and weakness of their knowledge of the laws and instructions and the complexity of the mechanism of income tax deduction itself and the number of laws associated with them. The research has made several recommendations, most notably the efficiency of accountants who calculate these taxes through the induction courses and the use of electronic programs designed for this purpose, and raising the efficiency of auditing systems, which is almost formal in achieving tax transparency. By addressing the gap between legal legislation and the accounting application of income taxes by direct deduction. And the need to provide a comprehensive and clear theoretical and professional framework that would contribute to raising the efficiency of the tax administration on the one hand, and to achieve the satisfaction and satisfaction of the taxpayer on the other hand.